Geometric Algebra for teaching AC Circuit Theory. (2nd September 2021) - Montoya, Francisco G.; Baños, Raúl; Alcayde, Alfredo; Arrabal‐Campos, Francisco M.
Summary: This paper presents and discusses the usage of Geometric Algebra (GA) for the analysis of electrical alternating current (AC) circuits. The potential benefits of this novel approach are highlighted in the study of linear and nonlinear circuits with sinusoidal and non‐sinusoidal sources in the frequency domain, which are important issues in electrical engineering undergraduate courses. The analysis and understanding of how AC circuits operate in steady state are of a paramount importance for all the electrical engineers and practitioners around the world. Typically, lecturers of most undergraduate courses teach circuit theory using complex phasors, vector calculus, or linear algebra. However, these approaches have some important limitations in practice, which requires the development of strategies to improve teaching‐learning process related to AC circuit analysis. By formulating a new mathematical framework, the paper presents and discusses how GA can be of help in this approach. It is also described how the results obtained by using GA are validated using computer‐based simulations. It is highlighted how the proposed teaching methodology based on GA theory can be effective in helping students learn AC circuit analysis since it has several potential benefits derived from its simplicity, compactness, and use of easily identifiable geometrical concepts. Abstract : We present a novel way to teach AC circuit theory under the paradigm of geometric algebra. By formulating this new mathematical framework, the paper presents and discusses how GA can be of help to avoid the limitations of the usage of complex algebra in nonsinusoidal AC circuits. It is also described how the results obtained by using GA are validated using computer‐based simulations. It is highlighted that the new approach improves teaching‐learning process related to AC circuit analysis.